COMP 250 Lecture 10 mathematical induction Sept. 29, 2017 1
For all π β₯ 1 , 1 + 2 + 3 + β¦ . + π β 1 + π = π(π + 1) 2 How to prove such a statement ? By βproofβ, we mean a formal logical argument that convincely shows the statement is true. Note that β convincely β is itself not well defined. 2
1 + 2 + β¦ + π β 1 + π Rewrite by considering π/2 pairs : 1 + 2 + β― + π 2 + ( π 2 + 1) β¦ + π β 1 + π If π is even, then adding up the π/2 pairs gives π/2 *( π + 1). What if π is odd? 3
What if π is odd? Then, π -1 is even. So, 1 + 2 + β¦ + π β 1 + π πβ1 ( 2 β π ) + π = πβ1 = ( 2 + 1) β π = π+1 2 β π which is the same formula as before. 4
Mathematical Induction Consider a statement of the form: βFor all π β₯ π 0 , π π is trueβ where π 0 is some constant and proposition π(π) has value true or false for each π . Mathematical induction is a general technique for proving such a statement. 5
β For all π β₯ π 0 , π π is trueβ For all π β₯ 1 , π(π+1) 1 + 2 + β¦ + π β 1 + π = 2 6
Mathematical induction requires proving two things: Base case: βP( π 0 ) is true.β Induction step: βFor any π β₯ π 0 , if P(π) is true, then P(π + 1) is also true.β 7
1 2 π 0 k k+1 Base case: βP( π 0 ) is true .β Induction step: βFor any k β₯ π 0 , if P(k) is true , then P(k+1) is also true.β The statement βP(k) is trueβ is called the βinduction hypothesisβ. 8
Base case: Induction step: For any k >= π 0 , if P(k) is true P( π 0 ) is true. then P(k+1) is true. 1 2 n0 k k+1 Thus we have proved: For any n >= π 0 , P(n) is true. 1 2 n0 k k+1
For all π β₯ 1 , Statement: 1 + 2 + 3 + β¦ . + π β 1 + π = π(π + 1) 2 Proof (base case, n=1): 10
For all π β₯ 1 , Statement: 1 + 2 + 3 + β¦ . + π β 1 + π = π(π + 1) 2 Proof (base case, n=1): 1(1+1) 1 = (true) 2 11
induction hypothesis is that P(π) is true: 1 + 2 + β¦ + π = π(π + 1) 2 Base case: Induction step: For any k >= π 0 , if P(k) is true P( 1 ) is true. then P(k+1) is true. 1 2 k k+1
Proof of Induction Step: ( 1 + 2 + 3 + β¦ . + π) + π + 1 by induction hypothesis π(π+1) + π + 1 = 2 = 13
Proof of Induction Step: ( 1 + 2 + 3 + β¦ . + π) + π + 1 by induction hypothesis π(π+1) + π + 1 = 2 π 2 + 1) (π + 1) = ( 1 2 ( π + 2 ) (π + 1) = Thus, π π ππ‘ π’π π£π πππππππ‘ π π + 1 ππ‘ π’π π£π. 14
Possible confusion π π has value true or false (Boolean). So, π π ππ‘ π’π π£π means what? 15
Examples β 3 = 2 + 1 β is true. β 3 = 2 + 2 β is false. 16
Examples β 3 = 2 + 1 β is true. β 3 = 2 + 2 β is false. βIf 3 = 2 + 2 then 5 > 7β is true. If this is a mystery to you, then I strongly advise you to take MATH 240 or MATH 318 (logic). 17
Mathematical Induction: Example 2 Prove the following statement: For all π β₯ 3 , 2π + 1 < 2 π . 2 π 2π + 1 π 0 1 2 3 4 18
For all π β₯ 3 , 2π + 1 < 2 π . Statement: Note: P( π ) is false for n= 1, 2. But that has nothing to do with what we need to prove. Proof (base case, π =3): 19
For all π β₯ 3 , 2π + 1 < 2 π . Statement: Note: P( π ) is false for n= 1, 2. But that has nothing to do with what we need to prove. Proof (base case, π =3): 2*3 + 1 < 8 (true) 20
For all π β₯ 3 , 2π + 1 < 2 π . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 21
For all π β₯ 3 , 2π + 1 < 2 π . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 2 π + 1 + 1 = ? 2π + 2 + 1 (This is 2π + 1 where π = π + 1 .) 22
For all π β₯ 3 , 2π + 1 < 2 π . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 2 π + 1 + 1 = 2π + 2 + 1 by induction hypothesis < 2 π + 2 23
For all π β₯ 3 , 2π + 1 < 2 π . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 2 π + 1 + 1 = 2π + 2 + 1 by induction hypothesis < 2 π + 2 < 2 π + 2 π , for k β₯ 3 This inequality is also true for k >=2 but we donβt care because we are trying to = 2 π+1 prove for k>=3. 24
Base case: Induction step: For any k >= π 0 , if P(k) then P(k+1). P( π 0 ) is true. 1 2 n0 k k+1 Thus, For any n >= π 0 , P(n) is true. 1 2 n0 k k+1
Example 3 Statement: For all π β₯ 5 , π 2 < 2 π . 2 π π 2 π 0 1 2 3 4 5 26
Statement: For all π β₯ 5 , π 2 < 2 π . Base case (n = 5): Induction step: 27
Statement: For all π β₯ 5 , π 2 < 2 π . Base case (n = 5): 25 < 32 Induction step: What do we assume ? What do we want to prove ? 28
Statement: For all π β₯ 5 , π 2 < 2 π . Base case (n = 5): 25 < 32 Induction step: What do we assume ? π 2 < 2 π , π β₯ 5 What do we want to show ? (π + 1) 2 < 2 π+1 29
Statement: For all π β₯ 5 , π 2 < 2 π . Base case (n = 5): 25 < 32 Induction step: (π + 1) 2 = π 2 + 2π + 1 30
Statement: For all π β₯ 5 , π 2 < 2 π . Base case (n = 5): 25 < 32 Induction step: (π + 1) 2 = π 2 + 2π + 1 by induction hypothesis < 2 π + 2π + 1 31
Statement: For all π β₯ 5 , π 2 < 2 π . Base case (n = 5): 25 < 32 Induction step: (π + 1) 2 = π 2 + 2π + 1 by induction hypothesis < 2 π + 2π + 1 by Example 2 < 2 π + 2 π = 2 π+1 32
Example 4 : Fibonacci Sequence 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, β¦. πΊ 0 = 0 πΊ 1 = 1 πΊ π + 2 = πΊ π + 1 + πΊ(π) , for π β₯ 0. Statement: For all π β₯ 0, πΊ π < 2 π 33
πΊ 0 = 0 πΊ 1 = 1 πΊ π + 2 = πΊ π + 1 + πΊ(π) , for π β₯ 0. Base case(s): π = 0: 0 < 2 0 is true. π = 1: 1 < 2 1 is true. 34
πΊ 0 = 0 πΊ 1 = 1 πΊ π + 2 = πΊ π + 1 + πΊ(π) , for π β₯ 0. Induction step: πΊ π + 1 = πΊ π + πΊ π β 1 by induction hypothesis < 2 π + 2 πβ1 35
πΊ 0 = 0 πΊ 1 = 1 πΊ π + 2 = πΊ π + 1 + πΊ(π) , for π β₯ 0. Induction step: πΊ π + 1 = πΊ π + πΊ π β 1 by induction hypothesis < 2 π + 2 πβ1 < 2 π + 2 π = 2 π+1 36
Recommend
More recommend